2002
DOI: 10.1046/j.1468-2982.2002.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Disturbances and Regional Cerebral Blood Flow Abnormalities in Migraine Patients: Their Relationship with the Clinical Manifestations of the Illness

Abstract: The purpose of the present study was to evaluate neuropsychological performance and regional cerebral blood flow in migraine patients, and to investigate whether possible abnormalities in any of these fields could be related to the chronicity of the disease. The sample included 60 patients and 30 healthy control subjects; all of them were subjected to a complete neuropsychological assessment, including emotional variables. In addition an interictal 99Tc-HMPAO SPECT was performed in 56 patients and 15 controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
184
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(206 citation statements)
references
References 28 publications
21
184
1
Order By: Relevance
“…One study assessed verbal memory and EF in active episodic CH (ECH) and reported only decreased auditory verbal memory as compared with tension headache patients (16), an impairment that could also be shown in migraine patients (17). As pain may interfere with cognitive performance (18), it is unclear whether pain itself (15) or the underlying headache pathology results in decreased test scores.…”
Section: Introductionmentioning
confidence: 99%
“…One study assessed verbal memory and EF in active episodic CH (ECH) and reported only decreased auditory verbal memory as compared with tension headache patients (16), an impairment that could also be shown in migraine patients (17). As pain may interfere with cognitive performance (18), it is unclear whether pain itself (15) or the underlying headache pathology results in decreased test scores.…”
Section: Introductionmentioning
confidence: 99%
“…In the adult population studies, Calandre et al 9 reported deficits of attention, memory, and information speed in migraineurs when compared to a control group. Le Pira et al 10 compared 30 individuals with migraine to a control group and showed that immediate and delayed memory were impaired in the migraine group.…”
mentioning
confidence: 99%
“…It was hypothesized that persistent abnormalities in cerebral blood flow causing neuronal disturbances and a complex neurotransmitter disorder may account for reduced short-and long-term memories in migraine patients [22,33]. However, other studies found neither detrimental cognitive effects in migraine patients nor differences between migraineurs with and without aura, when they were assessed interictally [34][35][36].…”
Section: Discussionmentioning
confidence: 99%